2010
DOI: 10.1016/j.breast.2009.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Factors contributing to improved local control after mastectomy in patients with breast cancer aged 40 years or younger

Abstract: Long-term local control rates were studied in a series of 659 patients with invasive breast cancer aged 40 years or younger, who underwent mastectomy in general hospitals in the southern part of the Netherlands between 1988 and 2005. During a median follow-up time of 6.0 years, 34 patients developed a local recurrence in the chest wall without previous or simultaneous evidence of distant disease. The 5- and 10-year actuarial local recurrence rates for the total group were 5.6% (95% confidence interval [95% CI]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
1
1
1
1
Order By: Relevance
“…The other series, unlike ours, report very little T3T4 (17,18). Lammers et al (18) reported 9% T3 and 2% T4. The advanced stages observed in the current series were determined to be associated with delays in diagnosis; frequently, patients consulted health structures in very advanced clinical phases explaining the predominance of the highly evolved stages.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…The other series, unlike ours, report very little T3T4 (17,18). Lammers et al (18) reported 9% T3 and 2% T4. The advanced stages observed in the current series were determined to be associated with delays in diagnosis; frequently, patients consulted health structures in very advanced clinical phases explaining the predominance of the highly evolved stages.…”
Section: Discussioncontrasting
confidence: 52%
“…Nodal invasion with capsular rupture in our series was found in 22.8% of cases and in 40% in the series of Bollet et al (16). The other series, unlike ours, report very little T3T4 (17,18). Lammers et al (18) reported 9% T3 and 2% T4.…”
Section: Discussionsupporting
confidence: 40%
“…The 10-year local relapse rate for women aged ≤40 years varies between 19% and 35% after BCT and between 7% and 12% after mastectomy [8,9,11,12,6]. In two previous reports concerning women ≤40 years we found 5-and 10-year actuarial local relapse rates of 9% and 17.9%, respectively, after BCT [13] and of 5.6% and 7.3% after mastectomy [14].…”
Section: Introductionmentioning
confidence: 79%
“…Lammers et al [104], sur une étude rétrospective de patientes de moins de 40 ans et traitées par mastectomie totale retrouvent globalement des taux de récidive locale à cinq et dix ans respectivement de 5,6 et 7,3 %. Ce taux diminue à 1,6 % à cinq ans en cas d'irradiation et dans les mêmes proportions en cas de chimiothérapie.…”
Section: Impact De La Mastectomie Totale Sur Le Contrôle Localunclassified